Synergy of energy alternatives, FinTech, and natural resources on SDG13: results from panel QCA and econometric models - Md. Mominur Rahman; Tasfia Tasneem Ahmed; Nafisa Binte Farid Prova; Sultan Ahmed (Discover Sustainability)
Abstract This study investigates the synergistic effects of energy alternatives, financial technology (FinTech), natural resources, and climate action within the BRICS nations, with a focus on achieving Sustainable Development Goal 13 (SDG13), which centers on climate action. The integration of system theory with panel Qualitative Comparative Analysis (QCA) and econometric methods enables a deeper exploration of how these factors interact to influence climate outcomes. The investigation is significant because BRICS countries—representing major emerging economies—are pivotal in global energy consumption, natural resource extraction, and financial systems, making them key players in the global transition towards sustainability. Identifying the configurational patterns of these variables and their impacts on climate action provides critical insights for policymakers aiming to balance economic growth with environmental sustainability. The findings reveal intricate configurations of conditions influencing climate action within the BRICS nations, highlighting the significance of factors such as renewable energy consumption, financial technology integration, and natural resources abundance. Econometric analyses further underscore the negative effects of fossil fuel energy consumption, positive effects of renewable energy consumption, financial technology, and natural resources abundance on climate action. This study contributes to the literature by integrating system theory into panel QCA and econometric analyses to provide a comprehensive understanding of the dynamics of climate action within the BRICS nations.